Research on differences and correlation between tensile, compression and flexural moduli of cement stabilized macadam - Yi Yang; Jianlong Zheng; Songtao Lu (Fracture and Structural Integrity)
In order to reveal the differences and conversion relations between the tensile, compressive and flexural moduli of cement stabilized macadam, in this paper, we develop a new test method for measuring three moduli simultaneously. By using the materials testing system, we test three moduli of the cement stabilized macadam under different loading rates, propose a flexural modulus calculation formula which considers the shearing effect, reveal the change rules of the tensile, compression and flexural moduli with the loading rate and establish the conversion relationships between the three moduli. The results indicate that: three moduli become larger with the increase of the loading rate, showing a power function pattern; with the shear effect considered, the flexural modulus is increased by 47% approximately over that in the current test method; the tensile and compression moduli of cement stabilized macadam are significantly different. Therefore, if only the compression modulus is used as the structural design parameter of asphalt pavement, there will be a great deviation in the analysis of the load response. In order to achieve scientific design and calculation, the appropriate design parameters should be chosen based on the actual stress state at each point inside the pavement structure.